(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Kashinskaya E. E. Review of dissertation researches on professional training future specialists of the hotel industry. The article presents an overview of researches devoted to the problems of professional training for the hospitality industry. Analysis of the scientific works of native and foreign scientists is conducted to determine the main directions of researches; study of the main problems which arise in the process of training future specialists of the hotel industry, and the extent of its solving; establishing the insufficiently investigated aspects of the field of professional education.